A lipid droplet-targetable and biothiol-sensitive fluorescent probe for the diagnosis of cancer cells/tissues. Issue 8 (24th March 2022) - Zhang, Yuewei; Zhang, Ning; Wang, Shuohang; Zan, Qi; Wang, Xiaodong; Yang, Qianqian; Yu, Xue; Dong, Chuan; Fan, Li
Abstract : We demonstrated for the first time the visualization of LD biothiols in surgical specimens from cancer patients. Abstract : Lipid droplets (LDs) have recently been reported as an attractive target for cancer diagnosis and treatment, owing to their special structure or microenvironment changes in cancer development and resistance. However, the relationship between the biothiol level of LDs and cancer is still poorly understood, partially owing to the absence of effective molecular tools. Herein, we developed a LD-targetable and biothiol-sensitive fluorescent probe, BTDA-RSS, by introducing 2, 4-dinitrobenzenesulfonyl (DNBS) as the biothiol reaction group into a benzothiazolyl derivative. BTDA-RSS displayed a marked and rapid fluorescence turn-on response toward biothiols, due to the biothiol-triggered cleavage of DNBS to yield the highly fluorescent benzothiazolyl iminocoumarin BTDA . In addition, the probe shows significant LD-targetable ability, and has been applied for imaging endogenous/exogenous biothiol changes in LDs. Importantly, BTDA-RSS has successfully been utilized to distinguish cancerous cells/tissues from normal cells/tissues with excellent contrast. Surprisingly, we demonstrated for the first time the visualization of LD biothiols in surgical specimens from cancer patients, thereby holding great potential for the application of BTDA-RSS in the clinical diagnosis of human cancers.